Economic Category “Business Efficiency” In the Modern Economic Paradigm - Alevtina Vasilievna KOROTKOVA1; Larisa Vitalyevna BAKULEVSKAYA1; Lyudmila Mikhailovna KORNILOVA2; Anna Sergeevna KORNILOVA2; Evgeniy A. IVANOV3; Maria Leonidovna TOLSTOVA2 (Communications of International Proceedings, 2021)
Category “efficiency” is one of the fundamental categories in economics. Its high importance is due, first, to the fact that efficiency is associated with the achievement of results, development goals, both of public production and private sector. In scientific research, interpretation of the concept of “efficiency” has become widespread, and today it is used in the following context: “performance”.
Keywords: Business Efficiency; Economic Category; Classification of Efficiency Types; Classification Criteria.